Effect of Dietary Supplementation of Carrot Meal on Survival, Growth and Pigmentation of Freshwater Ornamental Fish, Koi Carp, Cyprinus Carpio (L.) - Jain, Abhinka; Kaur, Vaneet Inder; Hollyappa, Shathanagouda Admane (Indian Journal of Animal Nutrition, 2020)
The study was conducted to assess the efficacy of experimental diets supplemented with carrot meal (CM) @ 1, 3, 5 and 7 % with respect to pigmentation, survival and growth in freshwater ornamental fish koi carp, Cyprnius carpio (Linnaeus)â€ for 120 days. Five diets including one control (CM0) without any supplemented carotenoid source and four supplemented experimental pelleted diets with 1% (CM1), 3% (CM3), 5% (CM5) and 7% (CM7) of powdered carrot in control diet were prepared. At the termination of the experiment, colouration studies indicated significantly higher (pâ‰¤0.05) skin and muscle carotenoid (Âµg g-1 wet weight basis) content in fish fed with CM5 (4.87) followed by diet CM3 (3.28), CM7 (2.78), CM1 (1.95) and CM0 (1.24). RGB colour intensity based on digital photographs analysis was also found to be highest in CM5 followed by CM3, CM7, CM1 and CM0. Fish growth in terms of % NWG, PER and SGR was highest in CM5 (94.09%, 1.48, 0.55) with lowest values of NWG and SGR in CM7 (65.71% and 0.41), while PER in CM1 (0.75). Further supplementation of CM @ 5% in Koi carp diet also improved the FCR (2.16) as compared to control (4.17). 100% survival of fish was recorded with diets supplemented with CM @ 3, 5 and 7 %, while it was 80 % in CM0 and CM1. During the experimental period, the water quality parameters did not vary significantly among control and treatments and remained in optimum range for fish growth. Hence, carrot meal can be supplemented in koi carp diet up to 5 % level both as colour enhancer as well as growth promoter under indoor rearing conditions.